Natural polymer‐based adhesive hydrogel for biomedical applications. Issue 2 (7th June 2022) - Long, Siyu; Xie, Chaoming; Lu, Xiong
Abstract: Hydrogel is a polymer network system that can form a hydrophilic three‐dimensional network structure through different cross‐linking methods. In recent years, hydrogels have received considerable attention due to their good biocompatibility and biodegradability by introducing different cross‐linking mechanisms and functional components. Compared with synthetic hydrogels, natural polymer‐based hydrogels have low biotoxicity, high cell affinity, and great potential for biomedical fields; however, their mechanical properties and tissue adhesion capabilities have been unable to meet clinical requirements. In recent years, many efforts have been made to solve these issues. In this review, the recent progress in the field of natural polymer‐based adhesive hydrogels is highlighted. The authors first introduce the general design principles for the natural polymer‐based adhesive hydrogels being used as excellent tissue adhesives and the challenges associated with their design. Next, their usages in biomedical applications are summarised, such as wound healing, haemostasis, nerve repair, bone tissue repair, cartilage tissue repair, electronic devices, and other tissue repairs. Finally, the potential challenges of natural polymer‐based adhesive hydrogels are presented.